RANCANG BANGUN PELAYANAN JASA SERVICE AC BERBASIS WEBMOBILE - Tayane, Rosalin Theophilia; Widodo, Widodo; Supriadi, Iyus; Rumakuay, Halik (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2024)
The implementation of information technology in business processes is a revolutionary step in facing competition in the era of digitalization. Instant lifestyle changes require businesses to be sensitive and flexible in understanding and meeting customer needs. As a business entity, CV Mandawi Jayapura Group, which operates in the field of AC installation and service, is required to be able to provide information technology-based services to make it easier for the public to obtain information regarding AC installation and service. The aim of this research is to create a webmobile-based AC service system. The method used in designing a service system is the waterfall method which starts from analyzing system requirements to identify problems in the running system, as well as knowing the needs of the system to be created. System design, where at this stage the system design process is carried out in detail. And implementation, where at this stage the coding process is carried out based on the system design that has been carried out. The result of this research is a web-based AC service information system that can make it easier for the public regarding information on service and AC installation services.